2016
DOI: 10.1002/pola.28180
|View full text |Cite
|
Sign up to set email alerts
|

Organic–inorganic poly(N‐vinylpyrrolidone) copolymers with double‐decker silsesquioxane in the main chains: Synthesis, glass transition, and self‐assembly behavior

Abstract: An organic–inorganic copolymer with polyhedral oligomeric silsesquioxane (POSS) and xanthate moieties in the main chain was synthesized via the polycondensation between 3,13‐di(2‐bromopropionate)propyl double‐decker silsesquioxane (DDSQ) and 1,4‐di(xanthate potassium)butane. This hybrid copolymer was used as the macromolecular chain transfer agent to obtain the organic–inorganic poly(N‐vinylpyrrolidone) (PVPy) copolymers via a reversible addition fragmentation chain transfer/macromolecular design via the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 70 publications
(109 reference statements)
0
9
0
Order By: Relevance
“…These difunctional POSS molecules have been successfully utilized to prepare the organic–inorganic hybrids via various polymerization approaches, most of which involve step-growth polymerizations. Recently, Zheng and co-workers , reported the combination of step-growth polymerization with controlled/living radical polymerization to introduce POSS cages into the main chains of polymers made from vinyl monomers, for example, poly­( N -isopropylacrylamide) and poly­( N -vinylpyrrolidone). It was of interest to note that the organic–inorganic copolymers displayed typical amphiphilicity and can self-assemble into the organic–inorganic hybrids nanoobjects in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…These difunctional POSS molecules have been successfully utilized to prepare the organic–inorganic hybrids via various polymerization approaches, most of which involve step-growth polymerizations. Recently, Zheng and co-workers , reported the combination of step-growth polymerization with controlled/living radical polymerization to introduce POSS cages into the main chains of polymers made from vinyl monomers, for example, poly­( N -isopropylacrylamide) and poly­( N -vinylpyrrolidone). It was of interest to note that the organic–inorganic copolymers displayed typical amphiphilicity and can self-assemble into the organic–inorganic hybrids nanoobjects in aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks assigned to chain unsaturation in copolymers occurred in the olefinic region (5.85-4.55 ppm). In the case of E/POSS copolymers, the 13 C NMR spectrum (Figure 7 b) showed the signals at 14.01 ppm (C1 in the spacer), 18.75 ppm (C2 in the These results are consistent with the lower catalytic activity of the ansa-metallocene system in ethylene copolymerization with POSS-10-3 or POSS-10-4 in comparison to ethylene homopolymerization and especially to copolymerization of ethylene with POSS-6-3 ( Figure 2). …”
Section: Structures Of E/poss Copolymersmentioning
confidence: 99%
“…Di-functional POSS derivatives have attracted considerable attention in recent years. Depending on the types of reactive substituents, they have been successfully incorporated into such macromolecules as polyimide [9][10][11], polysiloxane [12], polyamide [13], polyurethane [14], polysulfone [15], vinylidene-arylene copolymer [16], and polyethylene [17], via the polyethylene [17], via the step-growth polymerization process [9][10][11][13][14][15][16]18], or as pendant groups and cross-linkage sites through the coordination copolymerization [17].…”
Section: Introductionmentioning
confidence: 99%
“…The as-obtained Na 4 O 14 Si 8 (C 6 H 5 ) 8 was functionalized with the silylation reaction with dichlorosilane bearing a functional group, forming a class of so-called double-decker silsesquioxane (DDSQ) macromers. In the past few years, many difunctional DDSQ macromers carrying a variety of functional groups have been reported. More recently, Lee and Maleczka et al reported the synthesis of DDSQ macromers with an asymmetrically difunctionalized DDSQ macromer via selective protection with a boronic acid and then an isolation approach. To the best of our knowledge, nonetheless, the R groups ( viz.…”
Section: Introductionmentioning
confidence: 99%